Guidelines for the diagnosis and management of individuals with neurofibromatosis 1. Issue 2 (14th November 2006) - Ferner, Rosalie E; Huson, Susan M; Thomas, Nick; Moss, Celia; Willshaw, Harry; Evans, D Gareth; Upadhyaya, Meena; Towers, Richard; Gleeson, Michael; Steiger, Christine; Kirby, Amanda
Abstract : Neurofibromatosis 1 (NF1) is a common neurocutaneous condition with an autosomal dominant pattern of inheritance. The complications are diverse and disease expression varies, even within families. Progress in molecular biology and neuroimaging and the development of mouse models have helped to elucidate the aetiology of NF1 and its clinical manifestations. Furthermore, these advances have raised the prospect of therapeutic intervention for this complex and distressing disease. Members of the United Kingdom Neurofibromatosis Association Clinical Advisory Board collaborated to produce a consensus statement on the current guidelines for diagnosis and management of NF1. The proposals are based on published clinical studies and on the pooled knowledge of experts in neurofibromatosis with experience of providing multidisciplinary clinical and molecular services for NF1 patients. The consensus statement discusses the diagnostic criteria, major differential diagnoses, clinical manifestations and the present strategies for monitoring and management of NF1 complications.